2007
DOI: 10.1111/j.1742-1241.2007.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic side effects of antipsychotic medication

Abstract: The use of second-generation antipsychotics (SGAs) is associated with metabolic side effects including weight gain, diabetes mellitus and an atherogenic lipid profile. These adverse effects are not only the risk factors for cardiovascular disease, insulin resistance and diabetes mellitus leading to increased morbidity and mortality but may also impair the patient's adherence to treatment. SGAs in particular are associated with significant weight gain with clozapine and olanzapine carrying the highest risk, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
0
13

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(176 citation statements)
references
References 104 publications
5
157
0
13
Order By: Relevance
“…Some medications (e.g. antipsychotic drugs, glucocorticoids) have metabolic effects (on weight gain, lipid abnormalities, and glucose metabolism) (Tschoner et al 2007), and some medications (e.g. sleep medication and antidepressant drugs) have been shown to interfere with sleep characteristics (particularly sleep architecture) (Foral et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some medications (e.g. antipsychotic drugs, glucocorticoids) have metabolic effects (on weight gain, lipid abnormalities, and glucose metabolism) (Tschoner et al 2007), and some medications (e.g. sleep medication and antidepressant drugs) have been shown to interfere with sleep characteristics (particularly sleep architecture) (Foral et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging literature suggests an association of certain antipsychotics with the development of metabolic abnormalities (Allison and Casey, 2001 ;Jin et al, 2004;Dufresne, 2007;Meyer and Koro, 2004;Newcomer, 2005Newcomer, , 2007a. These metabolic abnormalities may in turn contribute to the higher risk of cardiovascular disease in patients with schizophrenia (Casey, 2005;De Nayer et al, 2005;Haupt and Newcomer, 2001;Hennekens et al, 2005;Jin et al, 2002Jin et al, , 2004Newcomer, 2005;Newcomer, 2007a;De Hert, 2005, 2007;Tschoner et al, 2007). However, the mechanism underlying antipsychotic-induced metabolic dysregulation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few data available on metabolic effects of amisulpride. Recent reviews concluded that amisulpride is associated with minimal weight change, ranging between 0.2 and 1.4 kg over varying treatment durations [Russell and Mackell, 2001;Tschoner et al 2007]. Amisulpride appears to have less risk of treatmentemergent dyslipidemia in compari son with olanzapine and clozapine [Newcomer, 2005;Rettenbacher et al 2007].…”
Section: Introductionmentioning
confidence: 99%